the DIGITAL FINANCIAL INNOVATION AND SHARIA BANKING FINANCIAL INCLUSION - Pahriati, Pahriati (Tawazuna, 2024)
Digital financial innovation refers to used benefit of information technology, like internet and mobile applications, provided financial services those are more efficient, accessible and affordable, and also   financial inclusion means providing access all levels of society, including those in remote or less developed area to have opportunity to use various services and financial products. This article uses qualitative research with datas collection techniques like searching in journals, articles and book that discuss digital financial innovation and islamic  banking financial inclusion. After collecting the data sources, the writer will analyze and draw conclusions is a result. Purposed of this research is to know how digital financial innovation is developing and how sharia  banking financial inclusion is, as well as obstacles and solutions in implementing digital finance